Pengaruh Kualitas Produk, Harga, dan Social Media Marketing terhadap Keputusan Pembelian Produk Skincare Scarlett Whitening dan Minat Beli Sebagai Variabel Intervening - Maulidiyah Ayu Saraswati; Matheous Tamonsang (JURNAL RISET MANAJEMEN (JURMA), 2024)
This research was conducted to examine the influence of product quality, price and social media marketing on purchasing decisions for Scarlett Whitening skincare products and purchase intention as an intervening variable (Case study of students from the Faculty of Economics and Business Class of 2020, Wijaya Kusuma University, Surabaya). The population in this study were active students of the Faculty of Economics and Business, Class of 2020, Wijaya Kusuma University, Surabaya. The sample used in this research was 60 respondents with the criteria being female and male respondents aged at least 17 years and respondents who had used and had purchased Scarlett Whitening skincare products. The sample collection technique uses non-probability sampling using purposive sampling, while data collection is carried out using a physical questionnaire. The analysis used is path analysis which is processed using IBM SPSS. The results of this research can be concluded that Product Quality has a partial effect on Purchasing Decisions with a significance value (0.000 < 0.05), Price has a partial effect on Purchasing Decisions with a value of significance (0.019 < 0.05), Social Media Marketing partially influences Purchase Decisions with a significance value (0.000 < 0.05), Purchase interest has a direct influence on Purchase Decisions with a significance value (0.022 < 0.05). Product Quality has a partial influence on Purchase Interest with a significance value of (0.008 < 0.05), Price has a partial influence on Purchase Interest with a significance value of (0.029 < 0.05), Social Media Marketing has a partial influence on Purchase Interest with a significance value of (0.001 < 0.05). Purchase Interest cannot be used as an intervening variable that explains Product Quality on Purchase Decisions with an influence of (0.082 > 0.017), Purchase Interest cannot be used as an intervening variable that explains the influence of Price on Purchase Decisions with an influence of (0.038 > 0.011) and Purchase Interest cannot used as an intervening variable that explains the influence of Social Media Marketing on Purchasing Decisions with an influence of (0.843 > 0.024).